Controllable automatic generation of non‐player characters in 3D anime style. (13th April 2022) - Li, Ruizhe; Oji, Ryo; Fujishiro, Issei
Abstract: Game creators always use prefabricated models as non‐player characters (NPCs) to create an atmosphere for game scenes. However, players are likely to see different NPCs with the same 3D models because creators usually cannot prepare a high number of NPC models for big game scenes. In this article, we present an anime‐like character customization system, where each customizing parameter can adjust the shape or color for the corresponding part of the character model. Based on this system, we propose an improved approach for generating a rich variety of 3D anime‐like NPCs including body models and clothing items in different styles. We introduce a neural network to control the facial appearances, Gaussian mixture models to control the colors of hair and clothes, and a Bayesian network to control the outfits of clothing items. We demostrate that the proposed approach can maintain the variety and stability of the generated characters. Abstract : Game creators always use prefabricated models as non‐player characters (NPCs) to create an atmosphere for game scenes. However, players are likely to see different NPCs with the same 3D models. We introduced a neural network, Gaussian mixture models, a Bayesian network to control their facial appearances, colors of hair and clothes, and outfits, respectively. It is demonstrated that the proposed approach can maintain the variety and stability of the generated characters.